The choice of law in torts - Ahern, John (Trinity College (Dublin, Ireland). School of Law, 2012)
In today’s increasingly global village, facilitated by the widespread availability of telecommunications, air, rail and road links, it is easy to make the assumption, particularly in multistate entities such as the United States of America and the European Union, that, from north to south and east to west, the provisions of substantive law would remain unchanged, unified and homogenous across those entities. The reality of today’s global village is, however, very different.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin